Transparent bamboo with high radiative cooling targeting energy savings - Zhou, Chengzhi (2021)
We have fabricated a bamboo-derived composite with enhanced radiative cooling via a simple solution-based process. The long-wavelength infrared emissivity (εLWIR) for one side is as low as 0.3, to prevent the heat exchange, and the εLWIR of the other side is near unity (0.95), to promote the radiative cooling. The energy saving simulations have been performed in Singapore, suggesting up to 89% energy savings enhancement, when compared with commercial low-E glass.